Efforts to Develop Students' Critical Thinking Skills in Chemistry Learning: Systematic Literature Review - Ruci Aditya Rushiana; Omay Sumarna; Sjaeful Anwar (Jurnal Penelitian Pendidikan IPA, 2023)
This article examines the efforts that can be made to develop students' critical thinking (CT) skills through chemistry learning. The method used in this study is the systematic literature review method, which consists of three stages: planning, conducting, and reporting. The planning stage is the stage of determining the topic, formulating the problem, and determining the criteria for the article to be used as a reference source. The conducting stage is the implementation stage of the systematic literature review and the reporting stage is the stage of writing systematic literature review articles. Based on the results of studies that have been conducted on 24 articles, it can be concluded that the learning model most widely used to develop students' CT skills in chemistry learning is project-based learning (PjBL). Other efforts made include implementing problem-based learning (PBL) models, guided inquiry, inquiry, predict observe explain (POE), REACT, the local culture-based 7E learning cycle, the ethnoscience-based chemistry learning model (MPKBE), and creative problem solving (CPS). The study's results also found that the characteristics of learning to develop students' CT skills in chemistry learning were using problems in everyday life (contextual) as motivation or stimulus and applying local wisdom-oriented learning.